A subjetividade na obra O Idiota de Dostoiévski no olhar de Emmanuel Lévinas da obra Autrement qu être ou au-delà de l essence - Santana, Maria Angelica (2011)
The present Thesis makes a comparative study between Lévinas and Dostoiévski, reflecting a philosophical category, that applied to the theology compromises in the defense of the human being: of its to think, to act and of its faith. In the categories of: "Another one", "To look at", "Alteridade", "Totalling", "Subjectivity" and "Responsibility", tematiza the relations and the interpersonal comprometimento. Leaving of Emmanuel Lévinas, French philosopher and Russian romancista Dostoiévski. The work is divided in four parts. First part: Lévinas and its commentators with the fenomenologia the category of alteridade and its constellations. Second part looks for to describe in general lines the thought of Lévinas being made a synthesis of Autramente qu' être or au-delà of L' essence, detaching the concept of subjectivity as decisive for its thought, while the third part intends to coadunar the thought of Lévinas with Literature and the Talmud. E the fourth part reflects an interface between Lévinas and Dostoiévski leaving conception that Lévinas conceives to the "other" as anti-symmetrical transcendência that restores the infinite responsibility of the subjectivity in face of the Other. In this direction, the thesis explains this interface enters Autramente qu' être or au-delà of L' essence e the romance The Idiot. Pointing out that Míchkin prince, main personage of The Idiot, in its enigmatic express "infantile" fragility ficcionalmente, the levinasiano concept of the "subjectivity and the substitution in the ethical drama", that is, it "hostage of the Other becomes"